MANAJEMEN PENDIDIKAN LINGKUNGAN BERBASIS NILAI QUR’AN-HADIS: KONSEP PENDIDIKAN ALAM DAN IMPLEMENTASINYA PADA LEMBAGA PENDIDIKAN - Dera Emilia Pratiwi; Mufatihatut Taubah (LP2M IAIN Sultan Amai Gorontalo, 2026)
Environmental education management based on Qur’anic and Prophetic values is a strategic approach that places divine principles as the foundation for organizing, planning, and implementing nature-based education within educational institutions. This concept stems from the Islamic view that nature is a sign of God (Qur’an 2:164; 55:1–13) that must be preserved, cultivated, and used as an ethical-spiritual learning medium. This study aims to explain the concept of environmental education from the perspective of the Qur’an and Hadith, as well as to analyze its implementation in educational institutions. The method employed is library research using a thematic (mawḍū‘ī) approach to verses and hadiths related to the environment, accompanied by descriptive analysis of environmental education management practices in several Islamic educational institutions. The findings indicate that key values—such as tawhid rububiyah, trust (amanah), ‘imārah al-ardh (earth cultivation), ecological responsibility, and ethical moderation—serve as the foundation for curriculum development, learning activities, and school culture. Implementation in educational institutions includes the integration of Qur’anic and Prophetic values into green curricula, habituation of environmentally friendly behavior, development of eco-pesantren programs, and community-based participatory management. This study underscores that environmental education management grounded in Qur’an-Hadith values strengthens students’ spiritual-ecological character and offers a sustainable educational model relevant to the challenges of the global environmental crisis.